RESEARCH ON THE ROLE OF BLIND PLEURAL BIOPSY IN DIAGNOSING THE ETIOLOGY OF TUBERCULOUS PLEURAL EFFUSION AT NGHE AN GENERAL FRIENDSHIP HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the diagnostic accuracy of closed (blind) pleural biopsy in identifying the etiology of tuberculous pleural effusion among patients with exudative pleural effusion at Nghe An General Friendship Hospital.Patients and Methods: A prospective diagnostic accuracy study was conducted on 49 patients with exudative pleural effusion who underwent closed pleural biopsy at Nghe An General Friendship Hospital from January 2025 to August 2025. The biopsy results (index test) were compared against a composite reference standard (including microbiology, and 6-month clinical follow-up) to determine diagnostic performance.Results: The male-to-female ratio was approximately 1.5/1, with a mean age of 65.9±19.6 years. Pleural effusion occurred on the right side in 61.2% of cases, the left side in 26.5%, and bilaterally in 12.3%. For the diagnosis of tuberculous pleural effusion, closed pleural biopsy demonstrated: sensitivity (Se): 80%; specificity (Sp): 100%; positive predictive value (PPV): 100%; negative predictive value (NPV): 82.8%.The most common complications were minor pneumothorax (12.2%) and subcutaneous emphysema (4.1%).Conclusions: Closed pleural biopsy is a highly reliable diagnostic method for tuberculous pleural effusion, particularly in medical facilities where medical thoracoscopy is unavailable. With a sensitivity of 80%, specificity of 100%, and a low rate of predominantly mild complications, it remains a valuable tool in clinical practice.
Keywords: Tuberculous pleural effusion, closed pleural biopsy, sensitivity, specificity, diagnostic accuracy